The Rooted Right: Power Bloc, Student Movement and Political Crisis in Bachelet’s Chile - Rojas, Gonzalo; Araújo Wanderley, Shimenny Ludmilla (Pontifícia Universidade Católica de São Paulo, 2016)
The general objective of this article is to analyze the Chilean power bloc in the two Bachelet-led governments of the Concertation (2006-2010) and the New Majority (2014-2016). The theoretical concepts used are economic-social formation, State, political power, power bloc and class struggle. Using a qualitative methodology, we adopt two hypotheses: the hegemonic fraction within the power bloc is the comprador bourgeoisie, which signals continuity between the Pinochet dictatorship and the Bachelet governments; the student movement during the Concertation government was dominated by secondary school students, whose demands were neutralized with institutional measures.